Pemanfaatan Arang Kayu, Tempurung an Sabut Kelapa Sebagai Bahan Bakar Pengasapan Ikan Nila (Oreochromis niloticus) Menggunakan Alat Pengasap Ikan Tipe Drum - Asmara, Sandi; Putri, Mustika; Oktafri, Oktafri; Kuncoro, Sapto (abe.fp.unila.ac.id, 2024)
Tilapia is a freshwater fish that is popular with many people, because its meat tastes savory and delicious. One way to process fish so that it lasts is by smoking the fish. This fish is smoked using a drum type smoker. This research aims to analyze the characteristics of smoked tilapia using several fuel components. The sample used was approximately 36 kg of fresh tilapia fish with fuel consisting of a composition of wood charcoal and coconut husks, wood charcoal and coconut shells, and a composition of coconut shells and coconut husks. The best treatment of the three fuel compositions used is the P2 treatment with a composition of 50% wood charcoal + 50% coconut shell, with an organoleptic value of appearance 8.60, aroma 8.33, taste 8.67 and texture 8.47, which means appearance whole, the color is less shiny, specific to the product, has a specific aroma of smoked fish that is less strong, has a specific taste of smoked fish that is less strong, and has a dense, compact texture, quite tight intertwining which has a weight loss of 35.5%, water content of 54.89% (in accordance with SNI), the yield is 64.49% and the amount of fuel used is 3.6 kg. Keywords: Coconut Fiber, Coconut Shell, Drum Type Smoker, Tilapia Fish Smoking, Wood Charcoal.